The traditional way of professional development in inclusive education: Still effective or not? - Suhendri Suhendri; Norimune Kawai (Journal of ICSAR, 2022)
Numerous studies suggest professional development to improve educators’ attitudes toward inclusive education. However, not all professional development seems to be effective in boosting participants’ attitudes. This current study is aimed to explore the effectiveness of professional development in inclusive education, especially for kindergarten principals in Indonesia. By conducting a 10-day professional development (n equals 60), the attitudes toward inclusive education of the participants were measured before and after the professional development using ITAIE (The Indonesian Teachers' Attitudes toward Inclusive Education). A paired T-Test was applied to find the differences in principals’ attitudes toward inclusive education before and after the professional development. The finding revealed no significant improvement in kindergarten principals’ attitudes toward inclusive education after joining the traditional way of professional development.